RBFOX2-regulated TEAD1 alternative splicing plays a pivotal role in Hippo-YAP signaling. Issue 15 (14th June 2022) - Choi, Sunkyung; Lee, Hyo Seong; Cho, Namjoon; Kim, Inyoung; Cheon, Seongmin; Park, Chungoo; Kim, Eun-Mi; Kim, Wantae; Kim, Kee K
Abstract: Alternative pre-mRNA splicing is key to proteome diversity; however, the biological roles of alternative splicing (AS) in signaling pathways remain elusive. Here, we focus on TEA domain transcription factor 1 (TEAD1), a YAP binding factor in the Hippo signaling pathway. Public database analyses showed that expression of YAP-TEAD target genes negatively correlated with the expression of a TEAD1 isoform lacking exon 6 (TEAD1 ΔE6 ) but did not correlate with overall TEAD1 expression. We confirmed that the transcriptional activity and oncogenic properties of the full-length TEAD1 isoform were greater than those of TEAD1 ΔE6, with the difference in transcription related to YAP interaction. Furthermore, we showed that RNA-binding Fox-1 homolog 2 (RBFOX2) promoted the inclusion of TEAD1 exon 6 via binding to the conserved GCAUG element in the downstream intron. These results suggest a regulatory mechanism of RBFOX2-mediated TEAD1 AS and provide insight into AS-specific modulation of signaling pathways. Graphical Abstract: